2017
DOI: 10.1186/s13717-017-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon pool trends and dynamics within a subtropical peatland during long-term restoration

Abstract: Introduction: The Florida Everglades has undergone significant ecological change spanning the continuum of disturbance to restoration. While the restoration effort is not complete and the ecosystem continues to experience short duration perturbations, a better understanding of long-term C dynamics of the Everglades is needed to facilitate new restoration efforts. This study evaluated temporal trends of different aquatic carbon (C) pools of the northern Everglades Protection Area over a 20-year period to gauge … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Differences between the responses observed in the Arctic and our temperate and subtropical lakes are most likely explained by the initial concentration and quality of terrestrially derived DOC and time. In the Arctic, glacial meltwater can be highly photolabile and dominated by seasonal inputs of DOC from shallow or deep soils (Cory et al, 2014;Spencer et al, 2014;and Kaiser et al, 2017). In temperate regions, DOC tends to contain more humic and fulvic acids derived from soils, which may be less photolabile than Arctic DOC.…”
Section: Dominant Degradation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between the responses observed in the Arctic and our temperate and subtropical lakes are most likely explained by the initial concentration and quality of terrestrially derived DOC and time. In the Arctic, glacial meltwater can be highly photolabile and dominated by seasonal inputs of DOC from shallow or deep soils (Cory et al, 2014;Spencer et al, 2014;and Kaiser et al, 2017). In temperate regions, DOC tends to contain more humic and fulvic acids derived from soils, which may be less photolabile than Arctic DOC.…”
Section: Dominant Degradation Processmentioning
confidence: 99%
“…However, DOC concentrations in Greenland lakes C. M. Dempsey et al: The relative importance of photodegradation and biodegradation (Saros et al, 2015) and the Mississippi River (Duan et al, 2017) have been decreasing. A long-term study of the Florida Everglades showed that some study sites were decreasing in DOC concentration, but the majority of sites were not changing (Julian et al, 2017). As DOC inputs into aquatic ecosystems have increased, stabilized, or decreased, long-term studies have focused on understanding the mechanisms behind the change, but less research has addressed the fate of DOC once it enters a lake.…”
Section: Introductionmentioning
confidence: 99%
“…Water column parameters such as total P (TP), total N (TN), and dissolved organic C (DOC) were analyzed for these samples. In the Everglades system, the organic C pool is predominately composed of the DOC fraction with low particulate OC concentrations (Julian et al 2017), therefore the bias of not including particulates in the C analysis is small. Individual soil samples were collected along the flow transects twice during the dry and wet seasons between 2015 and 2016 using the push-core method consistent with prior wetland soil studies (Bruland et al 2007;Osborne et al 2011a;Newman et al 2017).…”
Section: Data Sourcementioning
confidence: 99%
“…For this study we used the water column parameters total P (TP), total N (TN), and dissolved organic C (DOC) (Villapando and King 2018). In the Everglades system, the surface water organic C pool is predominately composed of the DOC fraction with low particulate OC concentrations (Julian et al 2017), therefore total OC is assumed to be equivalent to DOC concentrations. We also made use of soil samples collected along the flow transects twice during the dry and wet seasons between 2015 and 2016 and analyzed for TP, TN, and TC.…”
Section: Methodsmentioning
confidence: 99%